Final answer:
To rewrite the equation y + 4 = -2(x - 1) in slope-intercept form, distribute the -2 to x and -1 to get y + 4 = -2x + 2, then subtract 4 from both sides to solve for y, resulting in y = -2x - 2.
Step-by-step explanation:
To rewrite the linear equation y + 4 = -2(x - 1) in slope-intercept form, we need to solve for y and arrange the equation in the form y = mx + b, where m represents the slope of the line and b represents the y-intercept.
First, let's distribute the -2 to both x and -1:
y + 4 = -2x + 2
Next, we subtract 4 from both sides of the equation to solve for y:
y = -2x + 2 - 4
y = -2x - 2
Now the equation is in slope-intercept form, where the slope (m) is -2 and the y-intercept (b) is -2.